A–D–A‐Type Oligothiophenes for Small Molecule Organic Solar Cells: Extending the π‐System by Introduction of Ring‐Locked Double Bonds. (16th February 2015) - Fitzner, Roland; Mena‐Osteritz, Elena; Walzer, Karsten; Pfeiffer, Martin; Bäuerle, Peter
Abstract : A series of novel acceptor–donor–acceptor oligothiophenes terminally substituted with the 1‐(1, 1‐dicyanomethylene)‐cyclohex‐2‐ene (DCC) acceptor has been synthesized. Structural, thermal, optoelectronic, and photovoltaic properties of the π‐extended DCC n Ts ( n = 1–4) are characterized and contrasted to the trends found for the series of parent dicyanovinyl (DCV)‐substituted oligothiophenes DCV n T. The optoelectronic properties reveal the influence of the additional exocyclic, sterically fixed double bonds in trans ‐configuration in the novel DCC n T derivatives. A close correspondence for derivatives with equal number of double bonds, that is, DCC n Ts and DCV( n + 1)Ts, is identified. Despite having the same energy gap, the energy levels of the frontier orbitals, HOMO and LUMO, for the DCC‐ derivatives are raised and more destabilized due to the aromatization energy of a thiophene ring versus two exocyclic double bonds indicating improved donor and reduced acceptor strength. DCC‐terthiophenes give good photovoltaic performance as donor materials in vacuum‐processed solar cells (power conversion efficiencies ≤ 4.4%) clearly outperforming all comparable DCV4T derivatives. Abstract : A new series of acceptor‐substituted oligothiophenes (DCC n T) is investigated. Structural, thermal, optoelectronic, and photovoltaic properties are contrasted to dicyanovinylene‐capped oligothiophenes (DCV n T). Melting temperatures and solubilities are significantly enhanced for the DCC n Ts versus DCV n Ts. Oligomers with equal numbers of double bonds, show very similar absorption profiles. In vacuum‐processed planar heterojunction solar cells, DCC‐terthiophenes DCC3T and DCC3T‐Me show superior photovoltaic parameters compared to conjugated corresponding DCV‐quaterthiophenes.